1996
DOI: 10.1046/j.1365-2958.1996.395931.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cpsF and its product CMP‐N‐acetylneuraminic acid synthetase, a group B streptococcal enzyme that can function in K1 capsular polysaccharide biosynthesis in Escherichia coli

Abstract: Group B Streptococcus (GBS) is the foremost cause of neonatal sepsis and meningitis in the United States. A major virulence factor for GBS is its capsular polysaccharide, a high molecular weight polymer of branched oligosaccharide subunits. N-acetylneuraminic acid (Neu5Ac or sialic acid), at the end of the polysaccharide side chains, is critical to the virulence function of the capsular polysaccharide. Neu5Ac must be activated by CMP-Neu5Ac synthetase before it is incorporated into the polymer. We showed previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 42 publications
1
31
0
Order By: Relevance
“…The genes neu III B, neu III C, neu III D, and neu III A encode the final four proteins in the locus. Neu III D (formerly called CpsE) and Neu III A have been previously described (8,15). These four genes are most similar to the neuABCD genes from the gram-negative organism E. coli K1 (6) and the siaCAB genes of N. meningitidis serogroup B (11), which are responsible for the synthesis and activation of sialic acid for capsule production in these species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The genes neu III B, neu III C, neu III D, and neu III A encode the final four proteins in the locus. Neu III D (formerly called CpsE) and Neu III A have been previously described (8,15). These four genes are most similar to the neuABCD genes from the gram-negative organism E. coli K1 (6) and the siaCAB genes of N. meningitidis serogroup B (11), which are responsible for the synthesis and activation of sialic acid for capsule production in these species.…”
Section: Resultsmentioning
confidence: 99%
“…These four genes are most similar to the neuABCD genes from the gram-negative organism E. coli K1 (6) and the siaCAB genes of N. meningitidis serogroup B (11), which are responsible for the synthesis and activation of sialic acid for capsule production in these species. We previously demonstrated that neu III A encodes a CMP-NeuNAc synthetase, catalyzing the activation of sialic acid with CMP (15). Homologues of Neu III B are NeuNAc synthetases (2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Neu III C gene of GBS, however, complements ⌬neuC. It has also been shown that the Neu III A gene (previously designated cpsF) of GBS can complement a mutation in the E. coli K1 neuA gene, which encodes the CMP-N-acetylneuraminic acid synthetase (13). Indeed, a plasmid containing the four GBS genes involved in sialic acid synthesis, pDC128, successfully complemented strains with mutations in neuD, neuB, neuC, or neuA, the E. coli K1 region This result indicates that the sialic acid biosynthetic pathways for incorporation into capsular polysaccharides are probably identical in these two pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…GBS type III strain COH1, initially isolated from a newborn infant with sepsis, and S. pneumoniae serotype-2 strain D39 have been described previously (13)(14)(15)(16). All strains were grown on blood agar plates (REMEL).…”
Section: Generation Of Ethanol-inactivated Gbs and S Pneumoniaementioning
confidence: 99%